Potential for specific dihydropyridine calcium channel blockers to have a positive impact on cognitive function in humans: a systematic review - Peters,J; Booth,A; Peters,R (Therapeutic Advances in Chronic Disease, 2015)
Background: There is some evidence to suggest a possible association between calcium channel blocker (CCB) use and a lower decline in cognitive function compared with use of other hypertensive treatments. In particular, there is an emerging interest in the potential for specific CCBs, particularly the dihydropyridine CCBs nitrendipine, nicardipine, cilnidipine, lercandipine, nimodipine, azelnidipine and nilvadipine. The aim of this review was to assess the evidence relating to these specific CCBs and incident cognitive decline or dementia in humans.Methods: A systematic review of the literature was carried out. The databases MEDLINE, Embase and PsychINFO were searched from 1980 to 18 April 2014. All abstracts were reviewed by two independent reviewers.Results: From 753 unique records, 16 full text articles were examined and three retained. The three articles reported data from two studies. A 12-week double-blind randomized controlled trial of nitrendipine compared with cilazapril and a longer and larger double-blind placebo-controlled trial also of nitrendipine, namely the Systolic Hypertension in Europe trial (SYST-EUR). Nitrendipine was associated with a reduction in incident dementia in the SYST-EUR trial. There was no association seen for cognitive outcomes in the smaller trial.Conclusion: At present there is limited evidence to suggest that nitrendipine may be associated with reduction in incident dementia. This association comes from a single trial and needs to be replicated. Furthermore, there is no high-quality evidence for any of the other potential candidate CCBs.